2016
DOI: 10.4209/aaqr.2016.01.0044
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Visitors to the Indoor PM in the National Library in Prague, Czech Republic

Abstract: Temporal and spatial variation of size resolved particulate matter (PM) was measured in the Baroque Library Hall of the National Library in Prague during four intensive campaigns by an Aerodynamic Particle Sizer and three DustTrak instruments. The analysis showed, the indoor air can be considered as well mixed and therefore the simple mass balance model was used to estimate basic parameters (ventilation rate, deposition rates and penetration factors). The results revealed that the movement of visitors during v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Ludmila et al measured the concentration of particulate matter in the Baroque Library of the National Library of Prague, and used the CMB model to estimate the ventilation rate, deposition rate, and infiltration factors. The findings indicated that 35% of the indoor particulate matter content was attributable to tourists [8].…”
Section: Introductionmentioning
confidence: 98%
“…Ludmila et al measured the concentration of particulate matter in the Baroque Library of the National Library of Prague, and used the CMB model to estimate the ventilation rate, deposition rate, and infiltration factors. The findings indicated that 35% of the indoor particulate matter content was attributable to tourists [8].…”
Section: Introductionmentioning
confidence: 98%
“…Generated by various indoor and outdoor sources, they represent a complex mixture of particles that differ widely in chemical composition and size. Typical indoor sources in libraries and archives are related to activities conducted indoors (such as maintenance or cleaning) and in rooms accessible to public and visitors (skin and clothing abrasion, mineral particles brought on shoes) [1][2][3][4][5]. These processes are the principal sources of coarse particles (˃ 1 µm) composed mainly of organic and mineral matter.…”
Section: Introductionmentioning
confidence: 99%
“…Generated by various sources indoors and outdoors they represent a complex mixture of particles that differ widely in chemical composition and size. Typical indoor sources in libraries and archives are related to activities conducted indoors (such as maintenance or cleaning) and in rooms accessible to public and visitors (skin and clothing abrasion, mineral particles brought on shoes) [1][2][3][4][5]. These processes are principal source of coarse particles (˃ 1 µm) composed mainly by organic and mineral matter.…”
Section: Introductionmentioning
confidence: 99%